Modelagem Matemática na Educação Matemática: possibilidades para o ensino e aprendizagem da Matemática na Sala de Apoio à Aprendizagem - Tachevski, Cheila Miranda (2020)
This dissertation was dedicated to Mathematical Modeling from the perspective of Mathematical Education, conceived as a teaching methodology. The research subjects are students from the Support Room for Mathematics learning. The research center was centered around the following question: What possible contributions can Modeling in Mathematics Education make to the teaching and learning process of participants in the Learning Support Room? And the general objective of establishing Modeling as a methodological possibility of teaching and learning Mathematics in the Learning Support Rooms. In this context, to support the research stages, we delimit the following specific objectives: to analyze behavioral, interactive and learning issues found in students involved in Mathematical Modeling practices; to examine the evolution of the interest and performance of the participants in the face of practices with Mathematical Modeling, to understand how the performance of practices with Mathematical Modeling interferes in the teaching practice and to disseminate the results obtained in the investigation related to the adoption of Modeling in the Learning Support Rooms. The investigation was conceived according to a qualitative - interpretative perspective, with an outline according to Bogdan and Biklen (1994). The treatment of the data followed the proposal of Bardin (2011). Based on this design, we strive to understand, based on the data collected, using the concept of Burak (1992, 1994, 2008, 2010) for the development of practices with Mathematical Modeling, some aspects capable of enabling students to become protagonist in the teaching and learning process and the teacher an immersion in a new conception of the act of teaching. The results of this research indicate that the Mathematical Modeling in the adopted perspective, enabled the students of the Mathematics Learning Support Room to have a greater participation in classes and involvement with the activities developed during the meetings, a greater commitment to their own learning and a notable increase in responsibility for the requests made by the mathematics teacher. Learning was not limited to mathematical content, as these subjects had contact with art, culture, information technology and citizenship. The practices carried out also showed that the Modeling is also capable of molding or remodeling aspects related to the professional practice of the teacher that allows it to be adopted as a methodology.